Penguatan Karakter Integritas Siswa Melalui Lesson Study Dalam Upaya Pencegahan Bullying di SMP Negeri 2 Percut Sei Tuan - Pohan, Nurika Kholila; Jamaludin, Jamaludin (Jurnal Akuntansi Hukum dan Edukasi, 2024)
This study aims to determine the strengthening of students' integrity character through the Lesson Study model as an effort to prevent bullying at SMP Negeri 2 Percut Sei Tuan. Lesson study is a model for fostering the profession of educators and education personnel through collaborative and continuous learning assessments based on the principles of collegiality and mutual learning to build a learning community. This study is a type of qualitative research with a descriptive analysis method. Data collection techniques in this study are observation, interviews, and documentation. The results of the study obtained are that teachers have carried out their role as character builders through good and responsive responses to every report of bad treatment received by students. However, strengthening students' integrity character is still lacking due to the less than optimal implementation of lesson study. The implementation of lesson study at SMP Negeri 2 Percut Sei Tuan is still less than optimal due to the lack of teacher understanding regarding the importance of implementing the lesson study. Teachers still do not understand the stages of lesson study, namely plan (planning), do (implementation), and see (reflection).